Zur Rolle der Zweisprachigkeit in ausgewählten Textsorten - Jarosz, Józef (Studia Germanica Posnaniensia, 2019)
The paper deals with the role of multilingualism in selected text types. The reflections on forms of multilingualism and occasions for using multiple languages in a text lead to the creation of a typology that distinguishes between obligatory and optional use of multiple languages in text types. The obligatory multilingualism is constitutive in dictionaries, textbooks and teaching materials. Optional multilingualism, which was examined using the example of German advertising texts and grave inscriptions from Germany and Denmark, reinforces the main function of the text.